Irregular Migrant Access to Care: Mapping Public Policy Rationales. (17th June 2015) - Hall, Mark A.; Perrin, Jacob
Abstract: Both the USA and Europe limit access to care by undocumented immigrants ('irregular migrants' or IMs). In the debate over what level of access to confer to IMs, there are various public policy rationales operating either explicitly, or below the surface, ranging from minimalist humanitarianism to full cosmopolitan equality, with several intermediate positions between these two poles. This article informs the international debate by providing a conceptual mapping of these underlying policy rationales. Each position is based on different lines of reasoning or bodies of evidence, and each leads to somewhat different conclusions about the extent to which IMs should have access to different types of health care. It is unlikely that broad consensus will be achieved in this ongoing debate. However, by articulating the ethical, legal, pragmatic and conceptual reasons to support or oppose various positions, we hope to help determine where in the landscape of reasoned argument various positions lie, and how each position might be best supported or refuted. In particular, we see in this debate an illustration of Michael Walzer's classic analysis of competing spheres of justice. Various positions depend to a considerable extent on whether their advocates approach this issue from the health policy sphere rather than the sphere of immigration policy, or whether they attempt to blend the two spheres.